Praxe studijního programu Učitelství pro mateřské školy: metodická příručka pro studenty - Syslová, Zora (Masaryk University Press, 2021)
Title in English: Practice of the Study Program Teacher Training for Kindergartens: Methodical Handbook for Students The methodological manual was created with the aim of helping students of the bachelor's study program Teacher Training for Kindergartens to better understand the system of pedagogical and didactic practices so that they have a comprehensive idea of their organization and relationship to some theoretical subjects. At the same time, it should provide a deeper insight into the relationship between theory and practice through the portfolio and approach its function at the very end of the study, ie during the final state examination.